Network properties of intracortical myelin associated with psychosocial functioning in bipolar I disorder. (8th February 2022) - Sehmbi, Manpreet; Suh, Jee Su; Rowley, Christopher D.; Minuzzi, Luciano; Kapczinski, Flavio; Bock, Nicholas A.; Frey, Benicio N.
Abstract: Objective: Psychosocial functioning in bipolar disorder (BD) persists even during euthymia and has repeatedly been associated with illness progression and cognitive function. Its neurobiological correlates remain largely unexplored. Using a structural covariance approach, we explored whole cortex intracortical myelin (ICM) and psychosocial functioning in 39 BD type I and 58 matched controls. Method: T1 ‐weighted images (3T) optimized for ICM measurement were analyzed using a surface‐based approach. The ICM signal was sampled at cortical mid‐depth using the MarsAtlas parcellation, and psychosocial functioning was measured via the Functioning Assessment Short Test (FAST). Following construction of structural covariance matrices, graph theoretical measures were calculated for each subject. Within BD and HC groups separately, correlations between network measures and FAST were explored. After accounting for multiple comparisons, significant correlations were tested formally using rank‐based regressions accounting for sex differences. Results: In BD only, psychosocial functioning was associated with global efficiency ( β  = −0.312, p corr  = 0.03), local efficiency in the right rostral dorsolateral prefrontal cortex ( β  = 0.545, p corr  = 0.001) and clustering coefficient in this region ( β  = 0.497, p corr  = 0.0002) as well as in the right ventromedial prefrontal cortex ( β  = 0.428, p corr  = 0.002). All results excepting global efficiency remained significant after accounting for severity of depressive symptoms. In contrast, no significant associations between functioning and network measures were observed in the HC group. Conclusion: These results uncovered a novel brain–behaviour relationship between intracortical myelin signal changes and psychosocial functioning in BD.